NIR-II laser-mediated photo-Fenton-like reaction via plasmonic Cu9S8 for immunotherapy enhancement. (April 2022) - An, Lu; Wang, Chengbin; Tian, Qiwei; Tao, Cheng; Xue, Fengfeng; Yang, Shiping; Zhou, Xuesu; Chen, Xiaoyuan; Huang, Gang
Highlights: A strategy to enhance immunotherapy by NIR-II laser-mediated photo-Fenton-like reaction was proposed. Mild NIR-II laser (0.2 W/cm 2 ) irradiation efficiently excite plasmon-induced hot-electron transfer The valence conversion of Cu(II)/Cu(I) on plasmonic Cu9 S8 based on hot-electron transfer enhances CDT effectively. Enhanced CDT facilitates oxidative stress, induces immunogenic cell death and selectively enhances immunotherapy. Graphical Abstract: A mild NIR-II laser-mediated photo-Fenton-like reaction based on plasmonic Cu9 S8 is proposed for immunotherapy enhancement. NIR-II laser can promote the valence conversion of Cu(II)/Cu(I) of Cu9 S8 based on plasmon-induced hot-electron transfer for enhanced CDT, while the oxidative stress resulting from CDT induces immunogenic cell death and selectively enhances immunotherapy. ga1 Abstract: Chemodynamic therapy (CDT) is typically used to modulate the immunogenic tumor microenvironment and extend the benefits of immune checkpoint therapy because of its good tumor selectivity. However, the poor catalytic efficiency of CDT agents means that it often needs to be combined with other enhancement strategies, such as radiotherapy and photothermal therapy with high power density, which can inevitably traumatize normal tissues. To overcome these limitations, a near-infrared (NIR)-II laser-mediated photo-Fenton-like reaction based on a plasmonic self-doped semiconductor was proposed as a mild enhancement strategy to enhance the immune responses. Experimental simulations and results of plasmonic Cu9 S8 show that the NIR-II laser can enhance the CDT effect based on the plasmon-driven photoredox chemistry without inducing a photothermal effect. Furthermore, the enhanced CDT effectively induces immunogenic cell death and dendritic cell maturation both in vitro and in vivo . In addition, the antitumor immune response is greatly enhanced by the synergistic effect of the NIR-II laser in enhancing both CDT and anti-PD-L1. This allows for primary tumor elimination and the effective suppression of distant tumors and lung metastases. Our proposed design indicates that the NIR-II photo-Fenton-like reaction based on the plasmonic semiconductor effectively enhances CDT, thus selectively enhancing immunotherapy.